HAKIKAT REFERENSI DAN INFERENSI SEBAGAI PIRANTI LINGUISTIK PEMBENTUK KEUTUHAN WACANA - Labu Djuli; Jhon Bhae; Dewi I. N. Bili Bora; Fransiskus Bustan (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
This paper describes and explains the essence of reference and inference as the linguistic devices forming the unity of a discourse. The material of this paper is based on secondary data collected through library research and the method of data collection was a documentary study. The results of the study show that references and inferences as the linguistic devices are two external elements forming the unity of discourse that should be taken into account when someone wants to understand and interpret the meanings of the language used in a discourse of text of discourse. As such, it is required for him/her to know in more depth about the essence of reference and inference in line with their functions and significances as the external elements forming the unity of discourse.